Networking, Social Skills and Launching a New Business: A 3-Year Study of Nascent Entrepreneurs. (September 2022) - Klyver, Kim; Arenius, Pia
We combine insights from behavioral and skill perspectives on network agency to address how entrepreneurs' networking with close social ties and weak ties influences business launch, and the extent to which social skills strengthened or weakened these influences. Combining network perspectives previously developed in parallel, we fill in the gap of how well entrepreneurs are networking. We find frequent networking with close social ties increases entrepreneurs' chances of business launch when they have high social skills, but decreases their chances when they have low social skills, while networking with weak ties increases chances of business launch regardless of social skills.